Changes of myofibrillar protein structure improved the stability and distribution of baicalein in emulsion. (February 2021) - Chen, Jiahui; Xu, Yujuan; Pius, Bassey Anthony; Wang, Peng; Xu, Xinglian
Abstract: The effects of different dual frequency ultrasound treatment (DFUT) times (0, 2, 4, 6 and 8 min) on the structure of myofibrillar protein (MP) were investigated. Moreover, the effects of MP structure changes after DFUT on the stability and distribution of baicalein (BN) in emulsion were also evaluated. Results indicated that mild DFUT (≤6 min) promoted the unfolding of MP, thus increasing active sulfhydryl content (ASC), ζ-potential, and surface hydrophobicity (SUH). Moreover, secondary structure results showed that mild DFUT transformed MP from an α-helix to a β-sheet. Notably, the change of MP structures promoted the formation of stable emulsion, thus increasing the encapsulation efficiency (EEC) of BN in continuous phase. Also, BN in emulsion showed better storage stability and thermal stability after treatment. Overall, DFUT-modified MP can be used to establish a stable emulsion system, and it can be applied in embedding hydrophobic BN. Highlights: Effect of changes in MP structure on the stability of BN was investigated. Mild DFUT improved the stability and distribution of BN in emulsion. BN was stabilized by enhanced hydrogen bonding and hydrophobic interaction. Excessive DFUT was detrimental to the stability of a BN-based emulsion.